Behind the Scenes: The Corporate Governance Preferences of Institutional Investors - McCAHERY, JOSEPH A.; SAUTNER, ZACHARIAS; STARKS, LAURA T. (The Journal of finance (New York), 2016)
We survey institutional investors to better understand their role in the corporate governance of firms. Consistent with a number of theories, we document widespread behind-the-scenes intervention as well as governance-motivated exit. These governance mechanisms are viewed as complementary devices, with intervention typically occurring prior to a potential exit. We further find that long-term investors and investors that are less concerned about stock liquidity intervene more intensively. Finally, we find that most investors use proxy advisors and believe that the information provided by such advisors improves their own voting decisions.